The Serâbît Inscriptions: I. The Rediscovery of the Inscriptions - Lake, Kersopp (Harvard theological review, 1928)
In the spring of 1927 a small expedition, consisting of Professors Lake and Blake, Mrs. Blake, and the Reverend A. W. Johnson, went to Mt. Sinai to study the manuscripts in the Monastery of St. Catherine. Some results relating to our more immediate aim will be published later, but the most important outcome was entirely foreign to the original plan.